Glosa do wyroku Sądu Najwyższego z dnia 19 kwietnia 2021 roku (sygn. I CSK 40/21) - Fortuna, Franciszek Ignacy (Civitas et Lex, 2023)
The presented gloss relates to the judgment of the Supreme Court of 19 April 2021, ref. I CSK 40/21. There are two main issues in the case. The first issue relates to the admissibility of the second instance court considering the establishment of facts of the court of the first instance as its own in the case of an allegation of an incorrect evaluation of the facts raised in an appeal. The second issue, on the other hand, relates to the admissibility of the fact that the creditor has filed a bankruptcy petition as an automatic fulfillment of the exoneration condition. Although on the first issue, one may agree with the position of the Supreme Court that such an action of the court is acceptable, on the second issue it is not necessarily so. Despite the inconsistent position of the judicature in this matter, an analysis of the binding regulations and the doctrine allows one to conclude that such an interpretation is incorrect. The burden is on the member of the company’s board to prove the existence of any of the exemption circumstances. Filing a petition for bankruptcy by anyone does not relieve him of this responsibility.